SOIL FERTILITY ASSESSMENT OF AGRICULTURAL LAND IN THE ALMATY REGION USING GIS TECHNOLOGIES (ҚазҰУ Хабаршысы. География сериясы, 2023)
Being a strategically important and irreplaceable economic resource, today, agricultural land is the main source of raw materials for the agro-industrial complex. These features impose certain obligations on the state and land users to preserve the basic value of this category of land - its fertility. Taking into account the fact that Almaty region occupies an important place in the agricultural sector of the country, the effective use of agricultural land in providing food to the population of the territory remains an urgent problem.Reducing the utilization of agricultural land may lead to the creation of negative processes and will contribute to the decrease of fertility in the future, excluding farmland from intensive farm turnover. In the article, there are assessed the state of soils of agricultural land in the Almaty region based on the global system of digital mapping of soils using GIS technology, and the issues of improving the rational use of agricultural land in the region are considered. Specifically, maps of the degree of soil density, the content of organic carbon in the soil, the acidity, and characteristics of the distribution of chernozem in this area were developed using GIS technologies and based on data from a digital relief model, as a result of which the lands of the district of the region are classified into three groups and the dynamics of the specific gravity of the lands are presented.